Cohort profile: a data linkage cohort to examine health service profiles of people with intellectual disability in New South Wales, Australia. Issue 4 (12th April 2017) - Reppermund, Simone; Srasuebkul, Preeyaporn; Heintze, Theresa; Reeve, Rebecca; Dean, Kimberlie; Emerson, Eric; Coyne, David; Snoyman, Phillip; Baldry, Eileen; Dowse, Leanne; Szanto, Tracey; Sara, Grant; et al.
Abstract : Purpose: People with intellectual disability are a minority group who experience poorer physical and mental health than the general population and have difficulty accessing healthcare services. There is lack of knowledge about healthcare service needs and gaps experienced by people with intellectual disability. This study aims to interrogate a large linked administrative data set containing hospital admissions, presentations to emergency departments (ED) and mortality data to provide evidence to inform the development of improved health and mental health services for this population. Participants: A retrospective cohort of people with intellectual disability (n=51 452) from New South Wales (NSW), Australia, to explore health and mental health profiles, mortality, pattern of health service use and associated costs between 2005 and 2013. The cohort is drawn from: the Disability Services Minimum Data Set; Admitted Patients Data Collection; Emergency Department Data Collection, Australian Bureau of Statistics Death Registry and Registry of Births, Deaths and Marriages. Mental health service usage among those with intellectual disability will be compared to a cohort of people who used mental health services (n=1 073 139) and service usage other than for mental health will be compared with published data from the general population. Findings to date: The median age of the cohort was 24 at the time of the last hospital admission and 21 at the last ED presentation. The cohort has a higher proportion of men than women and accounts for 0.6% of the NSW population in 2011. Over 70% had up to 5 ED presentations and hospitalisations between 2005 and 2012. A high proportion of people with intellectual disability live in the most disadvantaged neighbourhoods. Future plans: Results will be used to inform the development of more responsive healthcare, including improved interactions between health, social and disability supports. More generally, the results will assist the development of more inclusive policy frameworks for people with intellectual disability.